Efektivitas Peranan Kepolisian Dalam Menanggulangi Tindak Pidana Perjudian - Muh Faidz Akhsan Rustam; Mulyati Pawennai; Ahyuni Yunus (Qawanin Jurnal Ilmu Hukum, 2020)
Abstract The results of this study indicate that the form of the effectiveness of the role of the police in tackling gambling crimes can be seen from the effectiveness of the roles played, including pre-emptive, preventive, and repressive. As for the obstacles faced by the police in the effort to overcome the crime of gambling, namely some people do not want to provide information to the police and the families of the perpetrators of closed gambling to provide information. Abstrak Hasil penelitian ini menunjukkan bahwa bentuk efektivitas peranan kepolisian dalam menanggulangi tindak pidana perjudian dapat dilihat dari efektivitas peranan yang dilakukan antara lain pre-emtif, preventif, maupun represif. Adapun hambatan yang dihadapi pihak Kepolisian dalam upaya menanggulangi tindak pidana perjudian yaitu sebagian masyarakat tidak mau memberikan informasi kepada pihak kepolisian dan keluarga pelaku perjudian tertutup memberikan informasi.